Glass transition temperature of polybutadiene and polyisoprene from high temperature segmental relaxation correlation using molecular dynamics - Sharma, Pragati; Roy, Sudip (Soft Materials, 2020)
Predicting glass transition temperature for rubber and rubber composites is immensely important for tire industry for the development of products and fine-tune process conditions. Molecular dynamics simulation is been used to predict glass transition temperature as a function of molecular-level structural changes, e.g., composition (functional groups), topology, and polymerization. However, prediction of glass transition temperature within experimental error bar from molecular dynamics simulation is only possible from all atomistic description (model) of the system as united atom and coarse-grained models under-predict the values. Conventional way of calculation of glass transition temperature from density (or any other properties which show sharp transition)-temperature plots are computationally very demanding because of atomistic simulations and simulations below the glass transition point, i.e., in glassy state. Here we report a novel method for calculation of glass transition temperature using only segmental relaxation correlation functions calculated at higher temperatures, i.e., above glass transition temperature. We have presented a protocol here and shown for two polymeric systems polybutadiene and polyisoprene. We believe this method cuts the computational cost of predicting glass transition temperature by one-third and will be applicable for industrial applications for structure-property validations.
Keywords: Glass transition temperature; molecular dynamics simulation; Polymers; rubber